Comparison of Body Mass Index with Modified Subjective Global Assessment for Detection of Malnutrition Among Patients Under Maintenance Hemodialysis: A Multi-Center Cross-Sectional Study - Rahman, Mohammad Syfur; Haque, Mohammad Farhadul; Sultana, Tayeba; Sultana, Tahera; Ul Alam, Syed Asif (Journal of Preventive and Social Medicine, 2022)
Background: Patients under maintenance hemodialysis are at increased risk of malnutrition, causing from multitude of factors. Present study aims to assess the prevalence of malnutrition among maintenance hemodialysis patients using both modified subjective global assessment score and body mass index, compare them and assess the sensitivity and specificity of body mass index for detecting malnutrition, along with determining a new cutoff value for BMI that better represent the maintenance hemodialysis patient’s nutritional status. Methods: This was a cross-sectional study conducted in the hemodialysis unit of Bangabandhu Sheikh Mujib Medical University, Sir Salimullah Medical College Mitford Hospital, BIRDEM General Hospital and National Institute of Kidney Diseases & Urology; among 80 adult CKD patients who were on regular (≥2 sessions per week) maintenance hemodialysis for more than 3 months without any acute infection, during the period of July 2016 to June 2017. Nutritional assessment was done for each patient using modified SGA score along with BMI. Sensitivity analysis of WHO recommended cutoff value for BMI was done among the study population using modified SGA score as gold standard test for detection of malnutrition among the respondents. ROC curve was used to estimate the best fitting cutoff value of BMI that showed highest sensitivity, specificity and accuracy for detracting malnutrition among maintenance hemodialysis patients. Results: The study participants were predominantly male (66.3%) and from age group 45 to 59 years (36.3%). Modified SGA score detected 90.0% of the study population as malnourished. WHO recommended 18.5 kg/m2 cutoff value was also used to detect malnutrition among study population and 13.8% were found to be malnourished, with a sensitivity and specificity of 12.5% and 75.0% respectively. Accuracy was found to be 18.8%. Using ROC curve, 23.1 kg/m2 was found to be the best fitting cutoff value of BMI for the study population to detect malnutrition. With a sensitivity of 47.2%, specificity of 37.5% and accuracy of 46.3%. Conclusion: BMI showed low sensitivity for detecting malnutrition among patients under maintenance hemodialysis, compared to modified SGA score and should be avoided as a screening tool, but 23.1 kg/m2 cutoff value for BMI showed potential to be used as an easy to use and quick tool for detecting malnutrition among such patients. Further study with larger sample size could shed more light on this. JOPSOM 2021; 40(1): 14-21